The THE REASON OF CODE-SWITCHING USED IN MY BASTARD PRINCE NOVEL - Maria Fitriana Starman; I Gusty Ayu Vina Widiadnya Putri; Ni Nyoman Deni Ariyaningsih (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
AbstractThe aims of this study to analyse the types and the reason of used code switching found in My Bastard Prince novel. This study used the theory proposed by Appel and Muysken (1987:118) to analysed the types of code switching and three types of code switching that occurs namely: tag switching, inter-sentential switching, and intra-sentential switching. meanwhile to analysed the reason of used code switching used the theory proposed by Hoffman (1991) and seven reasons are found namely: talking about particular topic, expressing feeling about something, expressing group identity, interjection, repetition used for clarification, quoting somebody else, and intention of clarifying the speech content for interlocutor. The most dominant type appear is inter-sentential switching and the less dominant is intra-sentential switching and descriptive qualitative method. Meanwhile for the dominant reason of the reason of code switching appear is expressing feeling about something, and for the less reason appear is repetition used for clarification.